STUDI PENGARUH VARIASI SUHU KALSINASI TERHADAP KANDUNGAN BATU KAPUR PARENGAN KABUPATEN TUBAN - Santoso, Toni Budi; Ikhwan, M. Zainul; Al Zakina, Bella Luthfiani; Sujiat, Sujiat; Rendra, Mrabawani Insan; Zainuddin, Zainuddin (Universitas Muhammadiyah Palembang, 2024)
The industrial and construction worlds utilize a lot of limestone from nature as a material. Easy utilization and abundant materials make limestone always attractive. Conventional processing is still a way to utilize limestone. In order to support more optimal utilization, laboratory-scale analysis is carried out. X-Ray Fluorescence (XRF) is an initial analysis to determine the limestone content. Calcination is carried out on limestone with the aim of changing its properties to be reactive with a planned calcination degree of 500?C. The original condition and conventional heating are used as samples as a comparison to the calcined limestone. The test results showed an increase in CaO content of 3% compared to the initial condition of the limestone, while SiO2 increased by 42%.